(untitled) - Sharma, S. K. (Darya Ganj, New Delhi, 2007)
Contents of material: 1/ Impact of IT revolution in libraries. 2/ Applications of electronic information resources. 3/ Digital archives. 4/ Digital reference services. 5/ Automated information services. 6/ Libraries and information society. 7/ Information retrieval in infoage
Keywords: Library science,Libraries,Information technology; Technological innovations,Information services,Automation,Information services